Social Media-Based Marketing Strategies and Their Impact on SME Sales Growth in Jember - Balthasar Watunglawar; Karnadi Karnadi; Amin Silalah; Katarina Leba (Journal of General Education and Humanities, 2026)
This study aims to examine the influence of social media-based marketing strategies on the sales growth of small and medium-sized enterprises (SMEs) in Jember Regency. In the era of digital transformation, social media has emerged as a strategic platform for businesses to reach broader consumer segments, strengthen customer relationships, and improve market competitiveness. This research adopts a quantitative approach using a survey method. Data were collected through questionnaires distributed to 120 SME owners and managers in Jember Regency who actively utilize social media as a marketing channel. The collected data were analyzed using simple linear regression analysis to determine the relationship between social media marketing strategies and sales growth. The findings reveal that social media-based marketing strategies have a positive and statistically significant effect on SME sales growth. The results suggest that effective social media use contributes to increased customer engagement, broader market penetration, and enhanced business performance. SMEs that consistently implement digital marketing practices tend to experience higher sales growth than those with limited social media activity. These findings highlight the strategic importance of optimizing social media platforms as an integral component of business development in the digital economy. The practical implications of this study emphasize the need for SMEs to prioritize high-quality content creation, maintain active customer interaction, and maximize the use of paid advertising features to improve promotional effectiveness and market reach. The study contributes to the growing body of literature on digital marketing by providing empirical evidence regarding the role of social media in supporting sustainable sales growth among SMEs in developing regions.